DERMAL AUTOGRAFT IN TREATMENT OF DEEP BURNS - L. P. Loginov; G. P. Titova; V. S. Borisov (Неотложная медицинская помощь, 2016)
The paper examines the results of transplantation of autologous graft and epidermal layer, grown outside the body of a patient, to granulating wounds after deep burns in 18 patients as well as methods which found no practical application due to poor healing abilities. It has been shown that the main cause of poor engraftment of the dermal graft is nutritional deficiency at the cellular level. This conclusion is confirmed by morphological studies of epidermal and dermal autograft. On the views of the authors, the further study of dermal autograft transplantation will put it to the worthy place among the other surgical methods restoring skin lesioned with burns.